2011
DOI: 10.37040/geografie2011116010023
|View full text |Cite
|
Sign up to set email alerts
|

Rural Areas – Living Space: Regional Differences in the Perceptions of Representatives of Rural Municipalities in Czechia Regarding Rural Areas

Abstract: This article seeks to contribute to discussion concerning the concept of countryside in geographical sciences. In the first section it discusses selected approaches for assessing rural areas and presents key stimulants from the new regional and cultural geography (rural areas as a socio-spatial process and as living space). The second section presents examples of empirical findings from a field survey, the respondents to which were mayors of rural municipalities – with up to 3,000 inhabitants – in Czechia. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 18 publications
0
16
0
Order By: Relevance
“…Length of life spent in the municipality might have a signifi cant impact on the response structure -but none of the categories deviated signifi cantly in our research. Although the MTAs close to country borders are located in the former Sudetenland (Boletice, Hradiště, Libavá) and were repopulated a er the expulsion of its original German population a er World War II, this fact is losing its importance nowadays (Chromý et al, 2011). Local residents without historical ties to the area have already built a relationship to it or have moved elsewhere.…”
Section: Survey Design and Its Methodological Limitationsmentioning
confidence: 99%
“…Length of life spent in the municipality might have a signifi cant impact on the response structure -but none of the categories deviated signifi cantly in our research. Although the MTAs close to country borders are located in the former Sudetenland (Boletice, Hradiště, Libavá) and were repopulated a er the expulsion of its original German population a er World War II, this fact is losing its importance nowadays (Chromý et al, 2011). Local residents without historical ties to the area have already built a relationship to it or have moved elsewhere.…”
Section: Survey Design and Its Methodological Limitationsmentioning
confidence: 99%
“…The presence of new religious communities can be seen in the emergence of new, often visually distinct, places of worship which transform urban space. Large cities tend to be more secularised and their religions more diversified than rural areas (due to a more liberal atmosphere, rationalisation, less social control, more options for leisure activities, more personal approaches to spirituality - Chromý, Jančák, Marada, Havlíček 2011;Potančoková, Berghammer 2015). Moreover, the religious landscape of Czechia, Slovakia and Poland is in many ways unique (Očovsky 1995;Bilska-Wodecka 2006;Havlíček, Hupková 2008), at least in a European context.…”
Section: The Role Of Post-secularism and Religious Identity In The Pementioning
confidence: 99%
“…Thirdly, there is neither consensus on which of the mentioned factors are suitable for characterizing the rural development (Clark et al, 1997) and whether to use weights to distinguish importance of factors. Chromý et al (2011) identified two approaches to define a rural area, broad and narrow. In broad approach, whatever is not urban is considered rural.…”
Section: Introductionmentioning
confidence: 99%
“…These rural areas also differ in socioeconomic, sociocultural or institutional environment. On the other hand, the narrow approach defines rural areas as areas with low population density and predominant primary sector (Jančák, 2003and Blažek, 2004In Chromý et al, 2011.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation